Morphological and Genetic Analysis of Momordica cochinchinensis (Lour.) Spreng. (Gac) from Different Accessions in Malaysia: Morphological and Genetic Analysis of Momordica cochinchinensis (Lour.) Spreng. (Gac) - Nurin Nazihah binti Mohd Khairi; Halimaton Saadiah Othman (Journal of Tropical Life Science, 2023)
Momordica cochinchinensis or gac fruit is a 'superfruit' that is well-known in Vietnam. Gac is an orange fruit that is ovoid in shape and has a soft spiny texture. In Malaysia, gac fruit is a new and less known plant. This study aimed to characterize gac fruit using morphological analysis involving both vegetative and reproductive parts and to characterize the genetic diversity in gac fruit by using Inter-simple sequence repeat (ISSR) analysis. Four different gac accessions were collected from different areas (Kota Damansara (Selangor), Melaka Tengah (Melaka), Hulu Langat (Selangor) and Kuantan (Pahang)) were cultivated under tropical conditions in Kuantan, Pahang. The gac accessions showed differences in morphological characters. Generally, the gac fruits were reddish-orange in colour, the leaf was dark green on the adaxial part and light green on the abaxial part, and the female and male flower was light yellow and white in color. The fruit weight ranged from 193.72 g (GD) to 334.70 g (GH) with varied shapes and spike density. DNA extraction was following the CTAB method. All 30 primers showed high levels of polymorphism (83%) and the polymorphism information content (PIC) with the mean of 0.48.Â Nei's genetic distance coefficient ranged between 0.27 and 0.6 with the mean value of 0.41. Dendrogram based on UPGMA analysis grouped the four gac accessions into two main groups. Cluster I consisted of accession GD, GM and GH while cluster II consisted of only GX. Results from both morphological and molecular analysis showed genetic diversities in all four gac fruits studied.